Sparse System Identification of Leptin Dynamics in Women With Obesity - Amin, Md. Rafiul; Pednekar, Divesh Deepak; Azgomi, Hamid Fekri; van Wietmarschen, Herman; Aschbacher, Kirstin; Faghih, Rose T. (Frontiers in Endocrinology, 2022)
The prevalence of obesity is increasing around the world at an alarming rate. The hypothalamus-pituitary-adrenal axis plays an important role in regulating energy balance and thereby contributes to obesity. The purpose of this research is to mathematically model and better understand the hormonal behavior leading to an energy equilibrium that contributes to obesity. To this end, we analyze the behavior of two neuroendocrine hormones, leptin and cortisol, in a cohort of obese patients, with simplified minimal state-space modeling. Using a system theoretic approach, co-ordinate descent method, and sparse recovery, we deconvolve the serum leptin-cortisol levels. Accordingly, we estimate the secretion patterns, timings, amplitudes, number of underlying pulses, infusion, and clearance rates of hormones in obese patients. Results demonstrate a negative causality between leptin and cortisol, based on the Granger causality test. These results indicate that increases in cortisol are prospectively associated with reductions in leptin, suggesting a negative inhibitory relationship. Reduced leptin may result in a decrease in satiety and thereby lead to obesity. Hence, investigation of leptin-cortisol dynamics will potentially help us to develop a treatment plan for individuals with obesity.